A randomized study to assess the efficacy of herbal product to prevent cisplatin-induced nephrotoxicity in a rat model - Eyup Veli Kucuk; Ahmet Bindayi; Meral Mese; Funda Gulcu Bulmus; Ergun Parmaksiz; Ali Cihangir Cetinel; Zerrin Bicik Bahcebasi; Kemal Sarica (Archivio Italiano di Urologia e Andrologia, 2017)
Objectives: This study aimed to investigate the protective effect and antioxidant activity of an herbal product that made from multiple plants in a rat model of kidney dysfunction induced by intraperitoneal cisplatin. Materials and methods: Twenty-four rats were divided into four different groups namely: Group 1 - control healthy animals without any specific medication, Group 2 - Herbal product only 5 mg/kg, Group 3 - cisplatin only and Group 4 - Herbal product 5 mg/kg + cisplatin. Results: Evaluation of our findings demonstrated a significant (p = 0.017) reduction in Catalase activities and a significant increase (p = 0.001) in renal tissue Malondialdehyde levels in cisplatin- treated rats when compared with the control group. Also, Glutathion and Glutathione peroxidase content revealed significant (p = 0.031) reduction in renal tissues of cisplatintreated rats compared with the control group. Pre-treatment of rats with the herbal product ameliorated these cisplatininduced changes of the antioxidant enzymes. No statistically significant changes were demonstrated in Superoxide dismutase activities in the tissue specimens of any group. Conclusions: This potent antioxidant herbal medicine was found to have potential antioxidant activity, which may in turn to be effective in the protection of kidney tissue resulting from cisplatin application. Therefore, much attention should be given to the possible role of natural dietary antioxidants for protecting the kidney.